Prototype Alat Olah Limbah Sistem Semi Batch Untuk Pengolahan Limbah Cair Laboratorium Kimia - Saipul Bahri; Ade Yulia Astuti; Ita Irawati; Mohammad Ryan Wahyudi; Dhau Aprilia Hakim; Meta Aprilia Saputri (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
Chemical laboratory liquid waste Environmental Pollution Control Techniques Cilacap State Polytechnic is liquid waste originating from practical or research activities of lecturers / students. Most of the waste contains organic and inorganic substances that are harmful to the environment. In the initial analysis the results of the wastewater content were in the form of lead less than 0.251 mg / L, Hardness 213.33 mg / L, TDS 4690 ppm, and pH 1.6. One parameter that needs to be addressed is TDS because dissolved solids can affect the O2 levels contained in the waters. In this research, a prototype of a waste processing tool was used to process the waste. In this research the method used is the process of coagulation, electrocoagulation and sedimentation in batch with a variation of residence time which affects the product. In addition, the filtration and adsorption process uses a continuous system, so that overall the tool uses a semi-batch system. In this study the chemicals used for processing were CaCO3 and citric acid. Then the adsorbent used is zeolite and activated charcoal as absorbent of dissolved solids. This waste treatment tool is considered quite effective in reducing TDS with a final result of 2950 ppm.